145k views
0 votes
Solve the following system of equations:

−2x + 4y = 6
y = 2x + 3

(1, 2)
(3, 3)
(−3, 0)
(−1, 1)

User Poidar
by
4.2k points

1 Answer

4 votes

Answer:

(-1,1)

Explanation:

We can solve this by either graphing and finding ther point the lines intersect, or mathematically, I'll do both.

Graphing:

Mathematically:

−2x + 4y = 6

y = 2x + 3

See the attached graph. The lines intersect at (-1,1)

--------------------

I'll rearrange the first equation (to make it easier for me):

−2x + 4y = 6

4y = 2x + 6

y = (1/2)x + 1.5

Now lets substitute the second equation into the first so that we can eliminate y:

y = 2x + 3

[(1/2)x + 1.5] = 2x + 3

- (3/2)x = (3/2)

x = -1

If x = -1:

y = 2(-1) + 3

y = 1

The solution is x = -1 and y = 1, or (-1,1)

=================

Both approaches give us (-1,1), the solution to the system of equations. It is the only point that satisfies both equations.

Solve the following system of equations: −2x + 4y = 6 y = 2x + 3 (1, 2) (3, 3) (−3, 0) (−1, 1)-example-1
User Misteryes
by
4.6k points